Evaluating the Impact of Digital Health Interventions on Diabetes Management in Indonesia - Pratama, Aditya (Generasi Sains Indonesia, 2024)
This study examines the impact of digital health interventions (DHIs) on diabetes management among patients in Indonesia, focusing on their effectiveness in improving clinical outcomes and identifying barriers to widespread adoption. Using a quantitative approach, data were collected from 300 patiets and analyzed for changes in HbA1c levels, while healthcare providers provided insights into the practical challenges of implementing digital tools. Results showed that high-frequency users of DHIs experienced significant improvements in glycemic control, with a mean reduction in HbA1c of 1.4%. However, challenges such as limited digital literacy, concerns about data privacy, and the need for training were identified as key barriers. Addressing these issues is essential for optimizing the use of digital health solutions and enhancing the accessibility of diabetes care in Indonesia. This study provides valuable insights for policymakers and healthcare providers aiming to integrate digital health more effectively into diabetes management strategies.